Identification and determination of ascorbic acid, free organic acids and tannic substances in the grass of Inula L. genus species - Yerenko, O. K.; Smoylovska, G. P.; Khortetska, T. V.; Єренко, Олена Костянтинівна; Смойловська, Галина Павлівна; Хортецька, Тая Володимирівна (My University, 2019)
The level of studying of Inula L. genus species, growing on the territory of Ukraine, is insufficient today. The study of chemical composition, accumulation of biologically active substances, pharmacological action of investigated grass species’ extracts of Inula L. genus of Ukrainian flora are of current interest. The aim of the work is making qualitative and comparative analysis of ascorbic, organic acids and tannic substances content in the raw material of investigated species of Inula L. genus (Inula britannica L. and Inula helenium L.). Quantitative determination was carried out by volume titration method. The presence of ascorbic acid, organic acids and tannic substances in the raw material of Inula L. genus investigated species was established with the help of paper chromatography and thin-layer chromatography methods. The quantitative determination of total organic acids was carried out according to XI edition of State Pharmacopoeia methods in terms of malic acid. Water extracts were studied for the tannins presence in raw material of Inula L. genus investigated species. Compounds identification was carried out through chemical reactions in accordance with Ukrainian State Pharmacopeia. The results obtained showed the perspective of further study of the biological activity of Inula britannica L. and Inula helenium L.
Keywords: Inula britannica L.; Inula helenium L.; paper chromatography; thin-layer chromatography; vitamin C; free organic acids; tannic substances